2016
DOI: 10.1111/inr.12262
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' communication with patients who are mechanically ventilated in intensive care: the Botswana experience

Abstract: A greater understanding of communication dynamics with the intensive care unit with patients who are mechanically ventilated is crucial to enable nurses to improve their care and improve patients' comfort. Incorporating communication in the nursing standards would ensure that patients are treated with dignity which would help improve patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 14 publications
2
35
0
2
Order By: Relevance
“…However, communication and direct contact with patients have also been described as being task‐oriented, brief, intensive and extensive in quantity (Meriläinen et al, ). Documentation of communication abilities reveals that patients both participate in and express desires about their emotional needs and medical treatment (Happ et al, ; Dithole et al, ). One study examined the effectiveness of a specific therapeutic way of communicating and found that psychological support based on positive suggestions may reduce the time patients spend on mechanical ventilation (Szilágyi et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, communication and direct contact with patients have also been described as being task‐oriented, brief, intensive and extensive in quantity (Meriläinen et al, ). Documentation of communication abilities reveals that patients both participate in and express desires about their emotional needs and medical treatment (Happ et al, ; Dithole et al, ). One study examined the effectiveness of a specific therapeutic way of communicating and found that psychological support based on positive suggestions may reduce the time patients spend on mechanical ventilation (Szilágyi et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…This study was a result of the findings from research [7] that has shown that communication between nurses and mechanically ventilated patients is minimal [8, 9]. These studies further established that short communication interventions are essential in augmenting communication skills among nurses working with mechanically ventilated patients in the ICU.…”
Section: Introductionmentioning
confidence: 66%
“…This study emerged as a result of the findings from research [7] which revealed minimal communication between nurses and mechanically ventilated patients in ICU, and others [8, 9] that demonstrate that short communication interventions are helpful in enhancing communication skills among nurses working with ventilated patients. Based on the recommendations from these studies [8, 9], it was deemed necessary to develop, implement, and evaluate a workshop-based program on communication skills for nurses, in order to help them attain the skills to communicate effectively with ventilated patients.…”
Section: Introductionmentioning
confidence: 90%
“…Albeit there are numerous alternative methods of communication available and approximately 50% of mechanically ventilated patients can be served by simple assistive communication tools, health care providers make little to no use of devices for these patients (Happ et al, ). In addition, there is paucity of studies focusing on the communication preferences of the registered nurses who experience communication difficulties with mechanically intubated patients (Dithole et al, ). Cognizant that the nurse‐patient communication is a dyadic process, the communication needs, anxieties, fears, and skills among nurses should also be considered in developing effective and appropriate interventions (Tejero, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of a therapeutic nurse-patient interaction, communication difficulty is a common phenomenon among mechanically ventilated patients (Dithole, Sibanda, Moleki, & Thupayagale-Tshweneagae, 2016;ten Hoorn, Elbers, Girbes, & Tuinman, 2016). Patients who are intubated and connected to a mechanical ventilator are deprived of speech and the ability to effectively communicate (ten Hoorn et al, 2016).…”
Section: Introductionmentioning
confidence: 99%